2012
DOI: 10.1038/mi.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-4, IL-13, and IL-17A differentially affect the profibrotic and proinflammatory functions of fibrocytes from asthmatic patients

Abstract: Fibrocytes contribute to the fibrotic changes most frequently observed in forms of asthma where inflammation is driven by T helper type 2 (Th2) cells. The mechanisms that regulate the profibrotic function of asthmatic fibrocytes are largely unknown. We isolated circulating fibrocytes from patients with allergen-exacerbated asthma, who showed the presence of fibrocytes, together with elevated concentrations of interleukin (IL)-4 and IL-13 and slightly increased concentrations of the Th17 cell-derived IL-17A, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
171
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(183 citation statements)
references
References 49 publications
10
171
0
2
Order By: Relevance
“…They participate in extracellular matrix (EM) remodeling through the production of some of the collagens and noncollagenous EM components synthesized in larger quantities by fibroblasts (Bucala et al, 1994;Chesney et al, 1998;Abe et al, 2001;Bianchetti et al, 2012b), and are also involved in collagen uptake and degradation (Bianchetti et al, 2012b). These cells can exhibit predominant proinflammatory activities or predominant profibrotic properties at tissue sites, depending on the host's response to diverse environmental insults (allergens, viruses, irritants) (Isgrò et al, 2013b) and on the characteristics of the local cell infiltrate and cytokine milieu (Bellini et al, 2012;Sazuka et al, 2014). Similarly to other cells with combined antigenpresenting function and mesenchymal cell-like features (Muñoz-Fernández et al, 2006;Saada et al, 2006), they acquire a myofibroblast-like phenotype in vitro and at the tissue sites because of the expression of adhesion molecules also present on the surface of these cells (Bianchetti et al, 2012b) and the inducible synthesis of the intracellular contractile protein α-smooth muscle actin (α-SMA) (Abe et al, 2001;Schmidt et al, 2003;Mori et al, 2005;Saunders et al, 2009).…”
Section: Background Information On Fc Identification and Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…They participate in extracellular matrix (EM) remodeling through the production of some of the collagens and noncollagenous EM components synthesized in larger quantities by fibroblasts (Bucala et al, 1994;Chesney et al, 1998;Abe et al, 2001;Bianchetti et al, 2012b), and are also involved in collagen uptake and degradation (Bianchetti et al, 2012b). These cells can exhibit predominant proinflammatory activities or predominant profibrotic properties at tissue sites, depending on the host's response to diverse environmental insults (allergens, viruses, irritants) (Isgrò et al, 2013b) and on the characteristics of the local cell infiltrate and cytokine milieu (Bellini et al, 2012;Sazuka et al, 2014). Similarly to other cells with combined antigenpresenting function and mesenchymal cell-like features (Muñoz-Fernández et al, 2006;Saada et al, 2006), they acquire a myofibroblast-like phenotype in vitro and at the tissue sites because of the expression of adhesion molecules also present on the surface of these cells (Bianchetti et al, 2012b) and the inducible synthesis of the intracellular contractile protein α-smooth muscle actin (α-SMA) (Abe et al, 2001;Schmidt et al, 2003;Mori et al, 2005;Saunders et al, 2009).…”
Section: Background Information On Fc Identification and Isolationmentioning
confidence: 99%
“…To address this issue, novel multiple parameter approaches have been developed that allow for the identification and sorting of a pure population of circulating and tissue Fcs by flow cytometry on the basis of the coexpression at high levels on the cell surface of CD45/CD45RO, CD34, CD11b, and CD13 (Bianchetti et al, 2012a;Isgrò et al, 2013a;2013b), which is a distinctive feature of Fcs (Bucala et al, 1994;Chesney et al, 1998;Isgrò et al, 2013b;Bianchetti et al, 2014). Taking advantage of these technical improvements, it has been possible to uncover many functional properties of isolated Fcs and improve our understanding of the molecular mechanisms and signaling pathways involved in their trafficking and activation in asthma (Bellini et al, 2012;Bianchetti et al, 2012a;Isgrò et al, 2013a;2013b), as discussed below.…”
Section: Background Information On Fc Identification and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Bellini et al 15 recently demonstrated that IL-17A increases proliferation of fibrocytes, the hematopoietic precursor cells involved in fibrosis 16,17 (Figure). Angiotensin II signaling may contribute to the pathogenesis of renal fibrosis by recruitment of fibrocytes in the bone marrow and by activating of these cells in the tissue.…”
Section: Guzik and Mikolajczyk γδ T Cells In Hypertensive Cardiac Damagementioning
confidence: 99%
“…Acute organ rejection is the most common, occurring within the first three months following transplantation; however, there may still be a risk of chronic rejection occurring several years later [12,24]. Chronic rejection is characterized by induction of fibroblast proliferation, pleomorphic effects (such as proliferation of smooth muscles) by some cytokines, maturation of B-cells and antibody synthesis by IL-4 [26][27][28]. Moreover, fibrosis formation is very common with chronic rejection due to the activation of the tissue repair process [29,30].…”
Section: Types Of Rejectionmentioning
confidence: 99%